Izbira lomnih testnih metod za karakterizacijo drobnozrnatega mikrolegiranega jekla Nioval 47 - Vojvodič-Tuma, Jelena (Kovine zlitine tehnologije, 1995)
In this article fracture test methods for determination of low-temperature range for the steel Nioval 47 are presented. The values of fracture toughness which are calculated by means of correlation expressions for various temperature ranges are in good correspondence to ASME ?$K_IC$? or ?$K_IR$? curves of ?$Marston^3$?.
Keywords: jeklo; mikrolegirana jekla; mehanika loma; žilavost